Effects of ozone exposure on lipid metabolism in Huh-7 human hepatoma cells - Peng, Jianhao; Wang, Siyuan; Wang, Yunlong; Yu, Wanchao; Zha, Yejun; Gao, Shuxin (Frontiers in Public Health, 2023)
Ozone pollution is a major environmental concern. According to recent epidemiological studies, ozone exposure increases the risk of metabolic liver disease.However, studies on the mechanisms underlying the effects of ozone exposure on hepatic oxidative damage, lipid synthesis, and catabolism are limited. In this study, Huh-7 human hepatocellular carcinoma cells were randomly divided into five groups and exposed to 200 ppb O3 for 0 h, 1 h, 2 h, 4 h, and 8 h. We measured the levels of oxidative stress and analyzed the changes in molecules related to lipid metabolism.The levels of oxidative stress were found to be significantly elevated in Huh-7 hepatocellular carcinoma cells after O3 exposure. Moreover, the expression levels of intracellular lipid synthases, including SREBP1, FASN, SCD1, and ACC1, were enhanced. Lipolytic enzymes, including ATGL and HSL, and the mitochondrial fatty acid oxidase, CPT1α, were inhibited after O3 exposure. In addition, short O3 exposure enhanced the expression of the intracellular peroxisomal fatty acid β-oxidase, ACOX1; however, its expression decreased adaptively with longer exposure times. Overall, O3 exposure induces an increase in intracellular oxidative stress and disrupts the normal metabolism of lipids in hepatocytes, leading to intracellular lipid accumulation.